Sustentabilidad de fincas productoras de cacao (Theobroma cacao L.) en el cantón Puebloviejo de la Provincia de Los Ríos - Pino Meléndez, Vanessa Elizabeth (2021)
The general objective of this research was: To evaluate the sustainability of cocoa-producing farms in the Puebloviejo canton, Los Ríos province, and as specific objectives: i) Build sustainability indicators based on pest management in cocoa cultivation, ii ) Characterize the cocoa-producing farms, with emphasis on pest management in the Puebloviejo canton of the Los Ríos province, Ecuador, iii) Determine the sustainability of the cocoa-producing farms established with national varieties and CCN 51. 8 indicators were constructed in the ecological dimension: Competition for weeds, incidence of insects-plagues, presence of insects that seriously affect the crop, diseases that mainly affect the crop, frequency of pesticide applications, type of agrochemicals applied, insect management -Pest / diseases, and Integrated Pest Management. The investigation of the characteristics of the producer and the cocoa-producing farms was carried out in 101 farms in the San Juan, Puebloviejo and Puerto Pechiche parishes, belonging to the Puebloviejo canton, in the Los Ríos province. The characterization determined important aspects of the producers, in the economic, ecological and sociocultural dimensions, among them, predominant gender, age, access to education, monthly income, destination of animal production, housing ownership and others. In the ecological dimension, the characterization carried out showed that Moniliasis is the main phytosanitary problem of cocoa, the mule ants (Atta. spp. and Acromyrmex spp.) are the main insects that affect cocoa and most of the cocoa crops they have a slight incidence of weeds, a majority group of cocoa producers carry out pest control combining cultural control and chemical control; in general, pruning is done once a year, most growers pile up diseased fruit and most do not use organic products. The characterization also allowed to know that the annual cocoa production varies, being <225 Kg / ha-1 (49%), most of the producers sell the cocoa in dry state (73%), they use ≤ 1 marketing channel (94%), have not received any type of credit from any source of financing (92%) and most of the cocoa trees do not have water for irrigation, that is, they depend on rainfall (62%). To determine sustainability, the economic, ecological and sociocultural dimensions were considered, the National cocoa producing farms obtained a General Sustainability Index (ISG) of 1,89, achieving a value of 3,0 only in the Sociocultural Indicator (ISC), the economic dimensions and ecological, reached an Economic Indicator (IK) of 1,2 and an Ecological Indicator (IE) of 1,5, respectively. The CCN-51 cocoa-producing farms, achieved a General Sustainability Index (ISG) of 2,26, reaching a value of 3,8 only in the Sociocultural Indicator (ISC), the economic and ecological dimensions, reached an Economic Indicator (IK) of 1,5 and an Ecological Indicator (EI) of 1,5, respectively. According to the research carried out on the 101 farms studied, 20% of the farms are economically sustainable, 4% ecologically sustainable, and 100% socioculturally sustainable. But only 1% of cocoa-producing farms met all the sustainability requirements, since in the methodology used, all dimensions must reach a value greater than 2 and the General Sustainability Index (ISG) must be greater than 2 The results show that important improvements must be made in the evaluated variables, especially in those that obtained values lower than 2, which will lead to the optimization of resources, aimed at improving the productive units in the Puebloviejo canton.